Using a combination of metronidazole and miconazole in correcting vaginal dysbiosis - Yu.E. Dobrokhotova; I.I. Ivanova (LCC «Medicine-Inform», 2018)
Using a combination of metronidazole and miconazole in correcting vaginal dysbiosis Yu.E. Dobrokhotova1, I.I. Ivanova2 1 Pirogov Russian National Research Medical University, Moscow, Russian Federation 2 CDC "Medsi in Krasnaya Presnya", Moscow, Russian Federation Bacterial vaginosis (BV) is the most common noninflammatory vaginal disease occuring in 80% of women of fertile age. BV may adversely affect reproductive function and often causes miscarriages, intrauterine fetus infection, complications after childbirth, abortion and invasive interventions on the genitals. Vaginal microbiocenosis is a dynamic and complex ecosystem, and the state of the vaginal microflora has a very serious effect on the health of women in general. The article describes the etiology, pathophysiology, clinical picture, diagnosis and treatment of BV and presents the results of the original study. Aim: analysis of subjective and laboratory parameters in patients with BV prior to the appointment of the drug metronidazole and miconazole (combined preparation Metromicon-Neo®) and 14 days after the therapy. Patients and Methods: 40 women aged from 20 to 45 years with vaginal microcenosis disorders participated in the study. Before and after treatment, complaints, results of microscopic examination and an outpatient test were carried out to determine the level of acidity of the vaginal contents. Results: before the treatment, the patients were mainly concerned about vaginal discharge with an unpleasant odor; complaints of burning, itching and discomfort in the genital area were less frequent, in all the women the vaginal pH was higher than 5.0. The smear tests microscopy revealed that the vaginal microflora was mainly represented by cocci, with a lot of clue cells, the presence of a large amount of epithelium was found in 12.5% of cases. After 14 days of using the Metronikon-Neo® suppositories the number of complaints decreased significantly, the vaginal pH was ≤4.5. According to the microscopic examination of the smear tests, the vaginal microflora has normalized. Conclusion: it was noted that Metromicon-Neo® is showed a positive result from the treatment (the clinical picture was normalized in 92% of cases, microscopic examination - in 94.2%) with good tolerance. Therefore, the indicator of the effectiveness of treatment with the drug Metromicon-Neo® can be assessed as high. Key words: bacterial vaginosis, vaginal microflora, pathological vaginal discharge, metronidazole, miconazole, Metromicon-Neo®. For citation: Dobrokhotova Yu.E., Ivanova I.I. Using a combination of metronidazole and miconazole in correcting vaginal dysbiosis. Russian journal of Woman and Child Health. 2018;1(1):82-87.